(untitled) (CIPEEX, 2024)
This paper presents the development of AgeFlex, a scheduling system for institutional environments. Its objective is to enhance space management in institutions, particularly in the educational sector. The introduction emphasizes the importance of technology in everyday life and its role as a tool to assist organizations in adapting to changes and remaining competitive. Within the academic context, efficient space management is essential to ensure proper organization and utilization. However, many institutions face challenges due to the complexity of scheduling and the increasing demand for different types of spaces. Ageflex emerges as a solution to optimize the scheduling process, making it more efficient and tailored to users’ needs. The system also aims to be safe and efficient, with a friendly interface that integrates perfectly with institutional routines. The solution uses technologies such as MySQL, PHP, and Laravel, with a focus on usability and integration, along with the implementation of the Entity Attribute Value (EAV) paradigm to enhance data flexibility. Ageflex aims to pave the way for more efficient and dynamic administration, maximizing resource utilization and delivering a satisfactory management experience.